2021
DOI: 10.3390/ijms22031492
|View full text |Cite
|
Sign up to set email alerts
|

From Liver Cirrhosis to Cancer: The Role of Micro-RNAs in Hepatocarcinogenesis

Abstract: In almost all cases, hepatocellular carcinoma (HCC) develops as the endpoint of a sequence that starts with chronic liver injury, progresses to liver cirrhosis, and finally, over years and decades, results in liver cancer. Recently, the role of non-coding RNA such as microRNA (miRNA) has been demonstrated in the context of chronic liver diseases and HCC. Moreover, data from a phase II trial suggested a potential role of microRNAs as therapeutics in hepatitis-C-virus infection, representing a significant risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 148 publications
0
21
0
1
Order By: Relevance
“…The C-index of 0.702 of the nomogram indicated that the prediction and observation results matched perfectly [ 26 , 27 , 28 ]. The calibration plot revealed a straight line approaching the diagonal, indicating a strong correlation between the actual and estimated probabilities at 1.3 and 5 years ( Figure 8 A).…”
Section: Resultsmentioning
confidence: 99%
“…The C-index of 0.702 of the nomogram indicated that the prediction and observation results matched perfectly [ 26 , 27 , 28 ]. The calibration plot revealed a straight line approaching the diagonal, indicating a strong correlation between the actual and estimated probabilities at 1.3 and 5 years ( Figure 8 A).…”
Section: Resultsmentioning
confidence: 99%
“…However, such strategies do not: alleviate the damage to the immune system caused by anti-tumor treatment strategies; exert a protective effect upon lymphocytes; help to improve the function of the immune system; protect immune-related stem cells or blast cells. In addition, patients with advanced HCC are often accompanied by different degrees of fibrosis, cirrhosis, functional insufficiency of the liver or portal hypertension ( Behary et al, 2021 ; Mohr et al, 2021 ; Raza et al, 2021 ). Therefore, patients need continuous infusion of albumin and immune enhancement to prevent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these miRNAs, which are involved in HBV transcription process, are also involved in the regulation of signaling pathways, disrupted in the cancer development. Among putative targets of miRNA-199a-3p are mTOR, c-Met, HIF-1α, CD44, ROCK1, and Axl, so this miRNA, being downregulated in miRNAs in Liver Cancer DOI: http://dx.doi.org/10.5772/intechopen.106171 liver cancer samples, may inhibit cell proliferation, migration, and invasion [69]. miRNA-184 may function as an anti-apoptotic factor in liver cancer, and INPPL1 was identified as one of its targets.…”
Section: Differential Expression Of Mirnas In Chronic Liver Diseasementioning
confidence: 99%